Preselection of polyploids using leaf methods in banana accessions - Jesus, Manuela Ramos da Silva de; Silva, Sebastião Oliveira e; Silveira, Daniela Garcia; Santos-Serejo, Janay Almeida dos; Sampaio, Antonio Hélder Rodrigues; Gimenez, Adonai Calbo (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate leaf methods to preselect banana putative polyploids in in vitro works with polyploidization. Leaf thickness, estimated from the specific masses of the fresh and dry matters of leaf disks, and leaf turgor, measured directly on the plants at 6:30 a.m. using the Wiltmeter equipment, were determined in diploid (Calcutta and Lidi), triploid (Grande Naine and Williams), and tetraploid (Bucanero and Calypso) banana. The evaluation of the DNA content was performed by flow cytometry, replacing the diploid Lidi by NBA, and the triploid Williams by Caipira. Genotypes with higher ploidy showed the highest fresh matter mass of the leaf disk. Leaf turgor potential was also significantly related to ploidy. Diploid genomes showed the lowest DNA contents (0.96 pg); the triploids Grande Naine (1.48 pg) and Caipira (1.63 pg), intermediate contents; and the tetraploids Calypso (1.90 pg) and Bucanero (2.26 pg), the highest contents. Fresh matter mass of leaf disks and leaf turgor, under proper irrigation management, can be used to preselect banana tetraploids in in vitro polyploidization studies.